Impact of excess air on the performance and emissions of an ethanol-fueled si engine - Ilminnafik, Nasrul; Saputra, Toni Haikal; Rozy Hentihu, Muhammad Fahrur (Jurnal Polimesin, 2025)
Ethanol-blended fuels, such as E60 (60% ethanol and 40% gasoline), have gained interest as an alternative to conventional fuels due to their potential to improve engine performance and reduce emissions. However, the effect of excess air on combustion characteristics remains a key factor in optimizing efficiency. This study investigates the impact of varying excess air levels on the performance and emissions of a 100 cc four-stroke spark ignition (SI) engine fueled with E60. The engine was connected to a Prony brake for performance testing, while exhaust emissions were analyzed using a gas analyzer. Results indicate that an excess air level of 22 L/m produced the highest power output (2.48 kW at 1600 rpm) and maximum torque (15.38 N·m at 1200 rpm). Additionally, at 22 L/m, the lowest fuel consumption of 0.110 kg/kWh and the lowest CO emissions were observed. However, at 23 L/m, a decline in performance was noted, likely due to incomplete combustion. The findings suggest that optimizing excess air in ethanol-fueled SI engines enhances performance and minimizes emissions. These insights contribute to the development of efficient combustion strategies for ethanol-based alternative fuels in small-scale transportation applications.